The Development and Preliminary Validation of a Brief Questionnaire of Psychopathic Personality Traits - Etzler, Sonja; Rohrmann, Sonja (Frontiers in Psychology, 2017)
The measurement of psychopathic personality traits via self-report has become an important tool in legal psychology. One prominent instrument is the Psychopathic Personality Inventory (PPI; Lilienfeld & Andrews, 1996), a well validated questionnaire that is widely applied in many countries. In Germany, it is the only questionnaire assessing psychopathic traits that is available from a publisher with a manual edited for easy administration. Nevertheless, the PPI shows certain shortcomings: the high number of 154 items makes it less economic, it was developed on a nonrepresentative undergraduate sample, and studies revealed an inconsistent factor structure. To overcome these points, a new questionnaire, the Questionnaire of Psychopathic Personality Traits (German: Fragebogen Psychopathischer Persönlichkeitseigenschaften; FPP) was developed. The sample consists of n = 132 civilians (56% female) and n = 173 inmates of German correctional facilities (30% female). The FPP comprises 30 items, whose wording was short and adequate for inmates. It shows satisfying psychometric properties regarding factorial structure, item properties, and reliability. Partial invariance regarding both subsamples allows for interpretation of latent means. Results supported validity such as associations with self-reported crime, and inmates’ misconduct. The factorial structure was cross-validated on a second sample of N = 517 participants (71% female) from an online study. The FPP is useful in large-scale research studies as well as for clinical settings, e.g., for treatment planning in correctional facilities.